2019
DOI: 10.1002/aur.2129
|View full text |Cite
|
Sign up to set email alerts
|

Diametrically opposed associations between academic achievement and social anxiety among university students with and without autism spectrum disorder

Abstract: Research findings indicate that anxiety, social anxiety in particular, is the most common experience reported by individuals with autism spectrum disorder (ASD) attending postsecondary education. Among students without ASD, higher levels of social anxiety have been postulated to correlate with impaired academic achievement; restriction of one's social network because of anxiety is thought to lead to reduction of access to resources important for learning such as social/emotional support and collaborative learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 74 publications
1
10
0
Order By: Relevance
“…For both groups, the negative association between higher levels of social anxiety and poorer academic and personal/ emotional adjustments is consistent with prior literature (Arjanggi and Kusumaningsih 2016;Brook and Willoughby 2015;Zukerman et al 2019). Previous findings have hypothesised that greater social anxiety may restrict an individual's access to social capital and access to information, resulting in poorer academic performance.…”
Section: University Transition Outcomessupporting
confidence: 88%
See 1 more Smart Citation
“…For both groups, the negative association between higher levels of social anxiety and poorer academic and personal/ emotional adjustments is consistent with prior literature (Arjanggi and Kusumaningsih 2016;Brook and Willoughby 2015;Zukerman et al 2019). Previous findings have hypothesised that greater social anxiety may restrict an individual's access to social capital and access to information, resulting in poorer academic performance.…”
Section: University Transition Outcomessupporting
confidence: 88%
“…Prior research findings on the impact of social anxiety on students’ academic and social transition outcomes have been mixed (Arjanggi and Kusumaningsih 2016 ; Brook and Willoughby 2015 ; Strahan 2003 ; Zukerman et al 2019 ). Some found greater social anxiety correlated with poorer academic adjustments, and suggested that highly socially anxious students may be unable to seek help for academic assignments, especially from those in a position of higher authority (e.g., teachers, tutors, or lecturers) (Arjanggi and Kusumaningsih 2016 ; Brook and Willoughby 2015 ; Zukerman et al 2019 ). However, others have found that greater social anxiety did not affect academic achievement at university, and suggested students are better at coping with academic compared to social challenges (Strahan 2003 ).…”
Section: Social Anxiety and University Transition Outcomesmentioning
confidence: 99%
“…Among neurotypical individuals in academic settings, more social interaction and broader social networks has been associated with greater psychological gains (social and emotional support) and academic gains (participating in collaborative learning) (Blansky et al 2013;Crosnoe et al 2003;Goguen et al 2010) leading to better academic achievements (Brook and Willoughby 2015). However, such rewarding outcomes may be less stimulating for people with autism, a population that is also characterized by diminished interest in collaborative activities, social anhedonia, and more restricted social networks, leading, possibly, to lower academic achievements (Chevallier et al 2012;van Asselt-Goverts et al 2015;Zukerman et al 2019b). Accordingly, it is possible that, among students with greater autistic features, social interactions are not perceived as likely to achieve favorable outcomes, and a larger gap between cognitive understanding of social behavior and actual social behavior elicits more social avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Three adult studies compared trait anxiety scores of participants on the autism spectrum with comparison group(s). Two studies (South et al, 2017;Zukerman et al, 2019a) included two comparison groups (1) NT participants with low anxiety, and (2) NT participants with high scores on self-reported general or social anxiety measures. South et al (2017) reported that the NT + anxiety group scored significantly higher on the STAI-T than both autism and NT groups, and the autism group scored significantly higher than the low anxiety NT group.…”
Section: Comparison Of Trait Anxiety Scores Between Groupsmentioning
confidence: 99%